An evaluation of turbulence model for vortex breakdown detection over delta wing - Setyawan Bekti Wibowo; Sutrisno Sutrisno; Tri Agung Rohmat (Archive of Mechanical Engineering, 2018)
An important phenomenon of delta wing is the mechanism of vortex core, which indicates the increase in lifting force until the occurrence of the vortex breakdown. The computational ﬂuid dynamics (CFD) is very helpful in visualizing and providing analysis of the detailed data. The use of turbulent models will aﬀect the quality of results in obtaining the vortex breakdown phenomenon. This study used several models of turbulence to capture the occurrence of vortex breakdown and compare it with experiments using water tunnel test facility. The results show that all turbulence models give good results at a low angle of attack (AoA), but at a high AoA the DES model gives the results closest to experimental ones with Cl error value of about 1 %. Taking into account the time required and the acceptable level of accuracy, the use of SST and k-ω models is an alternative option for use in the detection of vortex breakdown.